A retrospective study of ranula in two centres in Malaysia - Abdul Ghani, Norhaslinda; Raja Lope Ahmad, Raja Ahmad Al'konee; Abdul Rahman, Roslan; Mohd Yunus, Mohd Razif; Putra, SHA Primuharsa; Ramli, Roszalina (Elsevier, 2009)
Introduction: Ranula is a mucous extravasation cyst which occurs as a result of trauma or obstruction of the sublingual or minor salivary gland or the duct itself.